2009
DOI: 10.1002/cav.268
|View full text |Cite
|
Sign up to set email alerts
|

A new assessment methodology for virtual reality surgical simulators

Abstract: This paper presents an assessment methodology to validate surgical simulators which will help researchers in avoiding most common errors by providing a complete structured guide. The methodology organizes the questions depending on the validities they are related to, helping in objectives' definition and consistent hypothesis formulation. We will define the study depending on its purpose, time course and the study factor assignment, taking into account legal and ethical issues and choosing the population and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As a basis for the evaluation of VR surgical simulators, we propose the following methodology. More detail and a practical application can be found in [12].…”
Section: Methodology For the Evaluation Of Vr Simulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a basis for the evaluation of VR surgical simulators, we propose the following methodology. More detail and a practical application can be found in [12].…”
Section: Methodology For the Evaluation Of Vr Simulatorsmentioning
confidence: 99%
“…A thorough classification of different studies according to different criteria can be found in [12]. Here, we summarize them in Table 1.…”
Section: Methodology For the Evaluation Of Vr Simulatorsmentioning
confidence: 99%
“…Following on from concern over the adverse outcomes associated with the learning curve, and in the footsteps of the aviation industry, surgical training is increasingly embracing technological advances for the education and assessment of trainees. Various surgical virtual reality simulators are now available, which aim to teach and evaluate trainees performing both general and minimally invasive standardized surgical procedures [26]. Haptic technology assessing manual dexterity has been shown to correlate with the OSATS global rating score by Datta et al [27].…”
Section: Implications For Future Practicementioning
confidence: 99%
“…Second, specific surgical procedures are too complicated to simulate, given the software and hardware specification of early simulators. Recently, a commercial arthroscopy simulator called insightArthro VR was developed by GMV (Madrid, Spain) . It has been widely used in European countries and is considered to be an efficient tool for arthroscopic surgery training.…”
Section: Introductionmentioning
confidence: 99%